An unusual case of post-nasal "clicking" after pituitary surgery. (November 2020) - Tan, David Chi Hau; Robinson, Simon; Wickremesekera, Agadha
Highlights: Novel complication of disabling post-nasal clicking after endoscopic transphenoidal removal of a pituitary tumour. Unexpected anatomy of residual cleft with pneumocephalus. Obliteration required a third endoscopic procedure. Abstract: We report a case of a 64-year-old female who represented two months after pituitary surgery with the novel complication of intermittent disabling post-nasal pulsatile "clicking". Imaging and endoscopic examination showed a residual sella cleft with the tumour capsule and diaphragma cupping against the anterior sella bony defect with each pulsation, causing the clicking. The clicking resolved following second redo surgical endoscopic repair to jail a fat graft within the residual cleft with a central barricade of conchal cartilage graft and onlay standard repair.